Sistem Pegawai Pelayanan Tera/Tera Ulang Metrologi Legal Berbasis Mobile - Adip Miftaqul Ulum; Moh. Anshori Aris Widya; Munawarah Munawarah (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2023)
This research was carried out with the aim of explaining the implementation of a mobile-based legal metrology service system for employees and improving the quality of services for legal metrology at the Jombang Regency Office of Trade and Industry. With this mobile-based legal metrology service application, it can make it easy for employees to see the calibration and re-calibration schedule sent by the central metrology website and employees can send the results of the test and re-calibration directly in real-time without having to come to the metrology office. This research applies the waterfall method in its development, which is a systematic and structured approach involving a series of sequential stages. The results of this research created a mobile-based application for employees of the Jombang Regency Trade and Industry Office.